Motives, commitment and volunteering experience among Spanish university students - Valor Segura, Inmaculada; Rodríguez Bailón, Rosa (Anales de Psicología / Annals of Psychology, 2010)
University students are one of the social groups that are most involved in volunteering. This study was designed to explore some variables that facilitate why a person decides to become a volunteer. The study involved 168 participants and analyzed the influence of different motives on volunteering, the commitment the participants would be ready to take on, and previous experience as a volunteer. The results show the importance of different motives as the humanitarian interest in helping others in performing adequate volunteering work. Also according to the participants, esteem enhancement motives were the least important ones. Moreover, the findings emphasize the weight of previous experience in volunteering activities in ensuring a greater commitment to an organization.